Enhancing alfalfa photosynthetic performance through arbuscular mycorrhizal fungi inoculation across varied phosphorus application levels - Xia, Dongjie; An, Xiaoxia; López, Ignacio F.; Ma, Chunhui; Zhang, Qianbing (Frontiers in Plant Science, 2023)
This study evaluated the effects of arbuscular mycorrhizal fungi inoculation on the growth and photosynthetic performance of alfalfa under different phosphorus application levels. This experiment adopts two-factors completely random design, and sets four levels of fungi application: single inoculation with Funneliformis mosseae (Fm, T1), single inoculation with Glomus etunicatum (Ge, T2) and mixed inoculation with Funneliformis mosseae × Glomus etunicatum (Fm×Ge, T3) and treatment uninfected fungus (CK, T0). Four phosphorus application levels were set under the fungi application level: P2O5 0 (P0), 50 (P1), 100 (P2) and 150 (P3) mg•kg -1 . There were 16 treatments for fungus phosphorus interaction. The strain was placed 5 cm below the surface of the flowerpot soil, and the phosphate fertilizer was dissolved in water and applied at one time. The results showed that the intercellular CO2 concentration (Ci) of alfalfa decreased at first and then increased with the increase of phosphorus application, except for light use efficiency (LUE) and leaf instantaneous water use efficiency (WUE), other indicators showed the opposite trend. The effect of mixed inoculation (T3) was significantly better than that of non-inoculation (T0) (p < 0.05). Pearson correlation analysis showed that Ci was significantly negatively correlated with alfalfa leaf transpiration rate (Tr) and WUE (p < 0.05), and was extremely significantly negatively correlated with other indicators (p < 0.01). The other indexes were positively correlated (p < 0.05). This may be mainly because the factors affecting plant photosynthesis are non-stomatal factors. Through the comprehensive analysis of membership function, the indexes of alfalfa under different treatments were comprehensively ranked, and the top three were: T3P2>T3P1>T1P2. Therefore, when the phosphorus treatment was 100 mg•kg -1 , the mixed inoculation of Funneliformis mosseae and Glomus etunicatum had the best effect, which was conducive to improving the photosynthetic efficiency of alfalfa, increasing the dry matter yield, and improving the economic benefits of local alfalfa in Xinjiang. In future studies, the anatomical structure and photosynthetic performance of alfalfa leaves and stems should be combined to clarify the synergistic mechanism of the anatomical structure and photosynthetic performance of alfalfa.